The Influence of Crisis Management on Tokopedia User Loyalty (A Case Study of the Tokopedia X BTS Package Theft) - Natalia Adiva Hendaryanto; Satria Kusuma (Fakultas Komunikasi, Sastra, dan Bahasa, 2025)
Public Relations (PR) plays a crucial role in guiding organizations through crises, particularly through strategic crisis management that helps safeguard corporate reputation and maintain user loyalty. This study investigates the impact of PR-led crisis management on Tokopedia user loyalty in the context of the Tokopedia X BTS package theft incident. The research is grounded in Situational Crisis Communication Theory (SCCT) and consumer loyalty theory, and employs a quantitative method with statistical data analysis to examine the relationship between the two variables. Findings reveal that effective crisis management significantly influences user loyalty, particularly among emotionally engaged users such as BTS fans (ARMY). In addition to PR strategies, user loyalty is shaped by factors including consistent and responsive customer service, effective complaint resolution, trust in the platform, strong brand identity, and high user satisfaction. Features such as a user-friendly interface, competitive pricing, promotional offers (e.g., cashback, free shipping), and emotional connections—such as brand pride and identification with BTS—also contribute to loyalty. Furthermore, network effects and service innovation reinforce user retention. The results reflect a shift in consumer behavior, with users becoming increasingly critical and demanding. While this trend fosters deeper engagement and platform dependency, it also increases the potential for reputational crises. The study highlights the strategic importance of integrated PR crisis communication in shaping public perception and sustaining loyalty in the digital age.